2014
DOI: 10.3892/or.2014.3640
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-136 is associated with the primary cisplatin resistance of human epithelial ovarian cancer

Abstract: MicroRNAs (miRNAs) are involved in regulating the response of cancer cells to various therapeutic interventions, yet their involvement in the chemoresistance of human epithelial ovarian cancer is not fully understood. We found that miR-136 was significantly downregulated in specimens from patients with chemoresistant epithelial ovarian cancer. In the present study, we aimed to clarify the role of miR-136 in regulating the chemoresistance of ovarian cancer. Thirty-four tumor bank specimens and 2 well-establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…served low expression of miR-136 in patients with chemoresistant epithelial ovarian cancer [34]. Generally, it has been demonstrated that miR-136 was down-regulated in TNBC [35], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 82%
“…served low expression of miR-136 in patients with chemoresistant epithelial ovarian cancer [34]. Generally, it has been demonstrated that miR-136 was down-regulated in TNBC [35], which is consistent with our study.…”
Section: Discussionsupporting
confidence: 82%
“…In another study, overexpression of miR-136-5p negatively impacted proliferation of the LN229 glioblastoma cell line by downregulating matricellular cysteine rich angiogenic inducer 61 protein expression (23). miR-136-5p was also reported to be serve as an anti-oncogene in epithelial ovarian cancer (24). Gao et al (25) demonstrated that colorectal neoplasia differentially expressed is a target of miR-136-5p in colorectal cancer cells, and high levels of miR-136-5p may inhibit the migration and invasion of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of miR-136 suppressed migration, invasion and epithelial-to-mesenchymal transition in breast cancer cells (19). A study by Zhao et al (31) identified that miR-136 expression level was decreased in patients with primary platinum-resistant ovarian cancer tissues compared with that in platinum-sensitive ovarian cancer tissues. Additionally, miR-136 was identified as a tumor suppressor and miR-136 under expression in ovarian cancer improved chemo resistance partly via the inhibition of apoptosis and promotion of the repair of cisplatin-induced DNA damage (31).…”
Section: Discussionmentioning
confidence: 99%